2017
DOI: 10.3758/s13415-017-0542-8
|View full text |Cite
|
Sign up to set email alerts
|

Remembering specific features of emotional events across time: The role of REM sleep and prefrontal theta oscillations

Abstract: When an episode of emotional significance is encountered, it often results in the formation of a highly resistant memory representation that is easily retrieved for many succeeding years. Recent research shows that beyond generic consolidation processes, rapid eye movement (REM) sleep importantly contributes to this effect. However, the boundary conditions of consolidation processes during REM sleep, specifically whether these extend to source memory, have not been examined extensively. The current study teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 131 publications
(201 reference statements)
2
56
0
1
Order By: Relevance
“…Considering the emotional dimension, the selective sleep benefit for negative contextual memory is consistent with sleep's negative vs. neutral advantages for associative memories of temporal order 33 , and spatial location 32 , although these splitnight studies found this effect to depend on opposing sleep stages (NREM-rich early vs. REM-rich late sleep, respectively). More broadly, these observations fit with the notion that the sleeping brain preferentially processes information deemed of future relevance 7 .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Considering the emotional dimension, the selective sleep benefit for negative contextual memory is consistent with sleep's negative vs. neutral advantages for associative memories of temporal order 33 , and spatial location 32 , although these splitnight studies found this effect to depend on opposing sleep stages (NREM-rich early vs. REM-rich late sleep, respectively). More broadly, these observations fit with the notion that the sleeping brain preferentially processes information deemed of future relevance 7 .…”
Section: Discussionmentioning
confidence: 61%
“…Given that these studies focused on pairs of items, one possibility is that sleep's effects depend on whether the type of association tested relates to links with background contextual components (in which case sleep may favor the stabilization of links with negative memories), or links between individual items (in which case the emotional advantage may be suppressed or even reversed). Complicating this view, the aforementioned split-night study that found superior picture-location memory for negative vs. neutral items across late REM-rich sleep observed the opposite pattern across early NREM-rich sleep 32 . Another split-night study observed a similar early-night benefit for neutral picture-color associations, but did not observe this finding for picture-location associations (for which no differential negative/neutral or early/late sleep effects were found) 25 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations